Market choice behavior of fish farmers in the haor regions of Bangladesh (Annals of Bangladesh Agriculture, 2023)
The fish farming sector in haor regions of Bangladesh is integral to both local livelihoods and the national economy. This study examined the factors that influence fish farmers’ choice of market in this region, offering empirical insights into their decision-making processes. Using a random sampling technique, data were collected from 450 fish farmers across three upazilas in Netrokona, Kishoreganj, and Sunamganj districts. The multinomial logit model was employed to identify these influencing factors. The analysis revealed that factors such as age, education, access to extension services, and labor availability have negative effects on the selection of secondary markets. Total market loss also negatively impacts the choice of both secondary and tertiary markets. Furthermore, transportation facilities and distance to the market decrease the probability of selecting tertiary markets. In contrast, access to credit facilities positively influences the choice of secondary markets and negatively influences the choice of tertiary markets. Infrastructure facilities have a positive impact on the choice of secondary and tertiary markets but reduce the likelihood of selecting primary markets. This study underscores the importance of effective support systems, investments in education and infrastructure, risk management enhancements, and the promotion of sustainable practices in the local fish farming industry. Policymakers and stakeholders should consider these findings when developing strategies for the sustainable growth of the haor regions’ fish farming sector.Ann. Bangladesh Agric. (2023) 27 (2): 71-89